2017
DOI: 10.12659/msm.899553
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of 3 Nasal Packing Materials Used After Functional Endoscopic Sinus Surgery for Chronic Rhinosinusitis: A Comparative Study in China

Abstract: BackgroundThis study aimed to investigate the efficacy and safety of 3 nasal packing products (silicone tube, Beschitin-F, and Aquacel1-Ag) after functional endoscopic sinus surgery (FESS) for chronic rhinosinusitis (CRS) patients in China.Material/MethodsSixty-six CRS patients undergoing FESS surgery were randomly divided into 3 groups (22 patients in each group): the silicone tube group, the Beschitin-F group, and the Aquacel1-Ag group. Postoperative headache, nasal pain, nasal bleeding, and swelling of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These include but are not limited to sinusitis, epistaxis, synechia formation, and anosmia 71,76,101. Nasal packing is a commonly implemented intervention for improvement of hemostasis following ESS, and has been extensively investigated through RCTs and systematic reviews in recent years 102–106. Nasal packing has also been suggested as a component of routine operative care in patients undergoing TSA 107…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include but are not limited to sinusitis, epistaxis, synechia formation, and anosmia 71,76,101. Nasal packing is a commonly implemented intervention for improvement of hemostasis following ESS, and has been extensively investigated through RCTs and systematic reviews in recent years 102–106. Nasal packing has also been suggested as a component of routine operative care in patients undergoing TSA 107…”
Section: Discussionmentioning
confidence: 99%
“…71,76,101 Nasal packing is a commonly implemented intervention for improvement of hemostasis following ESS, and has been extensively investigated through RCTs and systematic reviews in recent years. [102][103][104][105][106] Nasal packing has also been suggested as a component of routine operative care in patients undergoing TSA. 107 The level of evidence supporting nasal packing after ESS has not yet been established in the TSA patient population.…”
Section: Nasal Packingmentioning
confidence: 99%
“…32,33 Many biodegradable material products, e.g., NasoPore, Cutanplast (Mascia Brunelli Spa, Milano, Italy), hyaluronic acid, and carboxymethylcellulose, have been developed to serve as nasal packings. [34][35][36][37] Biodegradable packings were reported to enhance sufficient hemostasis though facilitating water uptake or stimulating clotting. 4 Their dissolution occurred in a couple of days.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews also offered mixed evidence for improved granulation at the operative site. 11,14 More specifically, another study found that one type of chitosan-based hemostatic dressing was effective as a hemostatic agent across multiple DCR modalities. 15 A more recent addition to our practice, XeroGel (Entellus Medical Inc, Plymouth, Minnesota) is a biocompatible, dissolvable chitosan-based sponge that expands when hydrated to tamponade local intranasal structures, thereby minimizing postoperative bleeding and edema.…”
Section: Introductionmentioning
confidence: 99%
“…12 Induction of endothelin production and promotion of red blood cell and platelet adhesion contribute to barrier formation and wound sealing in the surgical setting. 13 Multiple systematic reviews reported that, unlike conventional packing or most other bioresorbable dressings, chitosan-based gel reduced synechiae following endoscopic sinus surgery. No impact on crusting or infection was observed.…”
Section: Introductionmentioning
confidence: 99%